Mutation and Variant of Coronavirus Disease 2019 (COVID-19): Review of Current Literatures - Susilo, Adityo; Jasirwan, Chyntia Olivia Maurine; Wafa, Syahidatul; Maria, Suzy; Rajabto, Wulyo; Muradi, Akhmadu; Fachriza, Ihza; Putri, Myranda Zahrah; Gabriella, Stacy (UI Scholars Hub, 2022)
Since March 2020, the Coronavirus Disease 2019 (COVID-19) pandemic has engulfed the world, including Indonesia, for nearly two years. SARS-CoV-2 has undergone several mutations during its evolution as a pathogen, resulting in various variants of global concern. Variants of this virus are suspected to impede the outbreak resolution and possibly causing the outbreak to spiral out of control. There is still considerable debate and research underway regarding the new SARS-CoV-2 variants. Rapid transmission mechanisms and widespread vaccination coverage have accelerated the virus’s mutation rate and resulted in numerous new variants. To date, this has resulted in the discovery of a new variant Omicron (B.1.1.529) in November 2021 in South Africa, which has since spread to 103 countries. Omicron is designated a Variant of Concern (VoC) due to its more powerful transmission than the previous variant. Although some information indicates that the symptoms associated with this variant are typically mild, the rapid transmission of Omicron can increase the next wave of COVID-19 cases. Additional research is required to determine transmissibility, pathogenesis, diagnosis, and proper management. As a result, we conducted an adjunct to studies on various COVID-19 mutations and variants until January 2022.